Visitors’ Perceptions of Tourism Impacts: Thai-Samakki Subdistrict, Wang Nam Keaw District, Nakorn Ratchasima Province - Phota, Ravinan; Phumsathan, Sangsan; Pongpattananurak, Nantachai (Kasetsart Journal of Social Sciences, 2015)
Understanding visitors’ perceptions of tourism impacts at tourism destinations can underpin proactive impact management strategies. The purposes of this study were to examine the tourism impact perceptions of visitors to Thai Samakki Subdistrict, one of the popular tourism destinations located in Dong Phayayen-Khao Yai, a natural world heritage site, and to determine the factors affecting their perceptions. In total, 800 questionnaires were distributed to domestic visitors. Fieldwork was conducted during August–December 2013. Overall, visitors recognized the positive impacts brought by tourism activities more than the negative side. Visitors perceived positive impacts at the high level. Increasing the income and revenue of local people and government, improving employment opportunities, and promoting visitors’ conservation awareness were the most positive perceived impacts, respectively. On the other hand, visitors perceived negative impacts at the moderate level. The most negative perceived impacts were trespassing on national park area by resorts, changing the natural landscape to tourism, and visual pollution from billboards, respectively. The results of ordinal regression analysis indicated that the negative impact perceptions of visitors were significantly influenced by their level of education, the number of sites that they visited, the season of travel, and awareness of world heritage value. Based on the study, it is recommended that management by the government sector needs to raise visitors’ awareness and appreciation of the world heritage site to improve their behavior to be more respectful of the natural area.